Clinical value of chest pain presentation and prodromes on the assessment of cardiovascular disease: a cohort study. Issue 4 (15th April 2015) - Robson, John; Ayerbe, Luis; Mathur, Rohini; Addo, Juliet; Wragg, Andrew
Abstract : Objectives: The recognition of coronary artery disease (CAD) among patients who report chest pain remains difficult in primary care. This study investigates the association between chest pain (specified, unspecified or musculoskeletal) and prodromes (dyspepsia, fatigue or dyspnoea), with first-ever acute CAD, and increased longer term cardiovascular risk. Design: Cohort study. Setting: Anonymised clinical data recorded electronically by general practitioners from 140 primary care surgeries in London (UK) between April 2008 and April 2013. Participants: Data were extracted for all patients aged 30 years and over at the beginning of the study period, registered in the surgeries. Main outcome measures: Clinical data included chest pain, dyspepsia, dyspnoea and fatigue, first-ever CAD and long-term cardiovascular risk (QRisk2). Regression models were used to analyse the association between chest pain together with prodromes and CAD and QRisk2≥20%. Results: 354 052 patients were included in the study. 4842 patients had first-ever CAD of which 270 reported chest pain in the year before the acute event. 257 019 patients had QRisk2 estimations. Chest pain was associated with a higher risk of CAD. HRs: 21.12 (16.68 to 26.76), p<0.001; 7.51 (6.49 to 8.68), p<0.001; and 1.84 (1.14 to 3.00), p<0.001 for specified, unspecified and musculoskeletal chest pain. Dyspepsia, dyspnoea or fatigue was also associated with a higher risk of CAD. Chest pain of all subtypes, dyspepsia and dyspnoea were also associated with an increased 10-year cardiovascular risk of 20% or more. Conclusions: All patients with chest pain, including those with atypical symptoms, require careful assessment for acute and longer term cardiovascular risk. Prodromes may have independent diagnostic value in the estimation of cardiovascular disease risk.